2019
DOI: 10.3390/ma13010004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Parameters of T-RTM on the Properties of Polyamide 6 Prepared by in Situ Polymerization

Abstract: With the rapid development of the automotive industry, there is also a significant need to improve the raw materials used. Therefore, the demand is increasing for polymer composites with a focus on mass reduction and recyclability. Thermoplastic polymers are preferred because of their recyclability. As the automotive industry requires mass production, they require a thermoplastic raw material that can impregnate the reinforcement in a short cycle time. The most suitable monomer for this purpose is caprolactam.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Recently, research has been conducted to develop advanced polyamide‐based composites using various reinforcements such as carbon fibers, glass fibers, natural fibers, carbon nanotubes, and graphene. [ 37 ]…”
Section: Reactive Thermoplastic Systems In Tp‐rtm Processmentioning
confidence: 99%
“…Recently, research has been conducted to develop advanced polyamide‐based composites using various reinforcements such as carbon fibers, glass fibers, natural fibers, carbon nanotubes, and graphene. [ 37 ]…”
Section: Reactive Thermoplastic Systems In Tp‐rtm Processmentioning
confidence: 99%
“…Models predictions and the experimental results on the unsaturated and saturated permeabilities are compared in Figure 8, where only the best fit among modeling and experimental data are reported. A nonlinear fit of the K 3 values as a function of fiber volume fraction has been performed using Equations ( 10) and (11), in order to obtain the fiber radius r f , whose values are reported in Table 4. The quadratic fiber arrangement is not able to properly model the experimental values, as inferred by the high differences reported in Table 4, since the obtained fiber radius is higher than the nominal value, which is equal to 3.35 µm for Preform A and 2.5 µm for Preforms B and C. Therefore, the fit obtained with the quadratic fiber arrangement with both the models are not reported in Figure 8 for the sake of clarity.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…The growing demand of polymer matrix composites in several fields has also driven the research and development of new manufacturing processes. The challenge of manufacturing high quality and complex geometry components at relatively low cost and fast cycle times has pushed toward the development of liquid composite molding (LCM) processes [10,11]. These technologies usually involve the use of dry reinforcement preforms, an assembly of dry fiber layers that have been pre-shaped to the form of the desired product and bonded together using a binder resin, which are impregnated by resin injection or infusion into a mold [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent studies on nanocomposites have revealed significant improvements in mechanical, tribological and thermal properties without increasing the density of nanocomposite. 11,12 The improvement in properties because of the high reinforcing efficiency of these nanoparticles due to large aspect ratio and enhanced interaction between the nanoparticles and matrix. A number of researchers have investigated the effect of zeolite on mechanical properties of polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamide 6 (PA6) is widely used as an engineering plastic due to its superior mechanical properties, tribological performance and chemical resistance. 12 Polyamide 6 nanocomposites have been successfully prepared and found to exhibit superior mechanical properties. 18,19 One of the major drawbacks of polyamides is their water absorption.…”
Section: Introductionmentioning
confidence: 99%